Analysis characteristic and performance of passive Radio Frequency Identification (RFID) for 13.56MHz system / Mohd Faizul Azmy Amat - Amat, Mohd Faizul Azmy (2007)
RFID (Radio Frequency Identification) is a technology that incorporates the use of electromagnetic or electrostatic An Radio Frequency Identification RFID system may consist of several component like tags and tags reader. Today world technology of RFID will used in a global security of identification systems. This thesis paper are presented the characteristic and performance of RFID for high range frequency coverage for passive RFID 13.56MHz system. Scopes of work include the algorithm for RFID flow in which frequency band will be continually implemented considering pre-determined constraints. Optimization process may also be required; hence optimization technique will also be incorporated in this work analysis. The objective and the goal of this final project paper to describe the characteristic and performance of 13.56MHz RFID system and to give a high level summary about its technological capabilities and the regulatory framework.